Prymnesiophytes of New Zealand's coastal waters : taxonomy, physiology and ecology : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology and Biotechnology at Massey University - Rhodes, Lesley Louise; Rhodes, Lesley Louise (Massey University, 1994)
Prymnesiophytes are an important component of the marine phytoplankton of New Zealand coastal waters, but there is little knowledge of the taxonomy, physiology or ecology of local strains. The Class comprises four orders which contain putative families and genera of the microscopic organisms, the microalgae. The Prymnesiophytes are known for their ability to explode in population numbers into "blooms"; one of New Zealand's most common bloom-formers is the coccolithophore Emiliania huxleyi (Prymnesiophyceae), which dominated the extensive phytoplankton blooms observed around New Zealand's coastline during 1993 - 94. Aspects of the physiology of and factors contributing to bloom formation in E.huxleyi are investigated. The phenomenon of seasonal blooms, a common occurrence amongst the microalgae, is reviewed. Studies of the blooms which occurred along the north-east coastline of New Zealand in 1992-93 showed that these were unusual events that were linked to the climatic conditions at that time, in particular cold sea temperatures associated with an "El-Niño" phase of the Southern Oscillation Index in the southern Pacific Ocean. The dominant microalgae were Gephyrocapsa oceanica (Prymnesiophyceae) and Fibrocapsa japonica (Raphidophyceae) and it is probable that the conditioning of the coastal waters by these microalgae had a role in the succeeding toxic event, in which human illnesses were definitively linked to shellfish toxins due to microalgae for the first time in New Zealand. Allelopathic, or chemical, interactions between microalgae were investigated in this study and Prymnesium parvum and P.patellifera caused inhibition of the growth of species from several microalgal classes. Unfortunately P.patellifera rapidly lost its inhibitory activity in vitro, but P.parvum remained active for several years in culture and was therefore selected as a positive control for the bioassays for ichthyotoxicity that were developed. The class Prymnesiophyceae includes toxic species of three genera, namely Chrysochromulina, Prymnesium and Phaeocystis. Ichthyotoxin bioassays based on toxin sensitive microalgae (Chattonella antiqua and Heterocapsa triquetra), shellfish larvae (Haliotis iris), brine shrimps (Artemia salina) and salmon erythrocytes (Oncorhynchus tshawytscha) were developed or refined and evaluated to enable the rapid and inexpensive detection of the haemolytic and cytolytic prymnesiophyte toxin, prymnesin. The novel quadriflagellate species C.quadrikonta, which bloomed in north-east New Zealand, May 1994, exhibited low levels of haemolytic activity in stationary phase cultures grown in standard nutrient medium (at 18°C, 100 μmol m-2s-1) as determined by the erythrocyte assay; no other Chrysochromulina species tested was toxic. Six locally occurring species were identified by electron microscopic examination of scales and light and electron microscopic observation of cultured isolates in this study. Seventeen of the nearly fifty named species of Chrysochromulina have now been identified in New Zealand. The average cell sizes and unmineralised spine scale lengths of the New Zealand isolates of C.ericina, C.hirta and C.quadrikonta were slightly larger than for their type species and the calcareous scales of E.huxleyi and G.oceanica were more heavily calcified than their northern hemisphere counterparts. No gradation of calcification with increased latitude was observed for the coccolithophores, as had been noted previously, and this might reflect the consistently lower sea temperatures prevailing, due to the unusually protracted "El-Niño" climatic conditions. Fluorescent probes proved to be useful tools for the differentiation of some morphologically-like species under the light microscope: Calcofluor white helped distinguish between cells of C.ericina and C.quadrikonta. The differentiation of the genera Prymnesium and Chrysochromulina was enabled through the specific binding of fluorescently-tagged wheat germ lectin to Chrysochromulina species. The growth characteristics and cultural idiosyncrasies of several southern hemisphere Chrysochromulina isolates have been described and compared with the toxic northern hemisphere relative, C.polylepis. C.polylepis, C.ericina and C. hirta fell into a temperate group on the basis of optimum growth rates (doublings d-1), while C.acantha, C.apheles, C.camella and C.quadrikonta fell into a sub-tropical group. All but C.acantha grew equally well with potassium nitrate, urea or ammonium chloride; C.acantha grew significantly slower with urea as nitrogen source. Only C.quadrikonta had a selenium requirement for growth. Maximum growth rates (doublings d-1) recorded in vitro were C.acantha, 1.2; C.apheles, 0.9; C.camella, 1.1; C.ericina, 1.5; C.hirta, 2.4 and C.quadrikonta, 1.4. The Chrysochromulina species and E.huxleyi and G.oceanica grew at low light intensities (25 μmol m-2 s-1), which could give these prymnesiophytes a competitive advantage in bloom situations, where shading due to the phytoplankton biomass can occur. The New Zealand isolate of G.oceanica grew optimally at salinities of 17 - 29°/oo, pH of 8.4 - 8.9 and temperatures of 20 – 25°C; E.huxleyi grew optimally at 29°/oo, pH7.5 - 8.9 and 15 – 25°C. G.oceanica grew equally well with ammonium chloride, urea or nitrate as nitrogen source; E.huxleyi grew optimally with ammonium chloride. Maximum growth rates recorded were 1.9 doublings d-1 for E.huxleyi and 1 4 doublings d-1 for G.oceanica.
Content removed due to copyright restriction: Jones, J. B., & Rhodes, L. L. (1994). Suffocation of pilchards (sardinops sagax) by a green microalgal bloom in wellington harbour, new zealand. New Zealand Journal of Marine and Freshwater Research, 28(4), 379-383. Rhodes, L. L., Haywood, A. J., Ballantine, W. J., & MacKenzie, A. L. (1993). Algal blooms and climate anomalies in north-east new zealand, august-december 1992. New Zealand Journal of Marine and Freshwater Research, 27(4), 419-430. Rhodes, L. L., O'Kelly, C. J., & Hall, J. A. (1994). Comparison of growth characteristics of new zealand isolates of the prymnesiophytes chrysochromulina quadrikonta and C.camella with those of the ichthyotoxic species C.polylepis. Journal of Plankton Research, 16(1), 69-82.
Keywords: Algae; Algal bloom; Prymnesiophyceae; Raphidophyceae; Microalgal growth